Report on the Incidence of Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Longer-term program engagement (LTPE) occurs when a member has spent at least seven of the past 10 years under Fund-supported financial arrangements. In response to the Executive Board's request for periodic updates on the incidence of LTPEs, this is the twelfth such report and provides information through June 22, 2011.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Sierra Leone